2009
DOI: 10.2174/1874940200902010008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Studies of Cellulolytic Activities Isolated from Planococcus Citri

Abstract: The study was performed to isolate the cellulolytic activities from a mealy bug Planococcus citri and to check their enzyme inhibition against leaf extract of Azdirachta indica and Buxus Sempervirens. Enzyme assay confirmed the presence of endoglucanase activity. Aqueous and non-aqueous fractions showed the maximum inhibition. Proteins containing fraction also reflected inhibition of activity that might lead to identification of some active peptides against cellulolytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…MvRL is also a chitin‐binding protein like MuBL and MuLL, but it is a mannose‐binding and ion‐dependent protein, unlike the M. urundeuva lectins, which indicates distinct mechanisms of carbohydrate recognition. Cellulase modulation by peptide molecules was also reported by Fayyaz‐ur‐Rehman et al ., who demonstrated that peptides isolated from aqueous extracts of Azadirachta indica and Buxus sempervirens leaves exerted an inhibitory effect on cellulases from the bug Planococcus citri . Those authors concluded that these leaves can be a source of peptides for the control of this insect.…”
Section: Discussionsupporting
confidence: 61%
“…MvRL is also a chitin‐binding protein like MuBL and MuLL, but it is a mannose‐binding and ion‐dependent protein, unlike the M. urundeuva lectins, which indicates distinct mechanisms of carbohydrate recognition. Cellulase modulation by peptide molecules was also reported by Fayyaz‐ur‐Rehman et al ., who demonstrated that peptides isolated from aqueous extracts of Azadirachta indica and Buxus sempervirens leaves exerted an inhibitory effect on cellulases from the bug Planococcus citri . Those authors concluded that these leaves can be a source of peptides for the control of this insect.…”
Section: Discussionsupporting
confidence: 61%
“…On citrus, P. citri damages plants by feeding on roots, bark, foliage and fruit [2]. During feeding P. citri injects toxic saliva into plants and extracts phloem sap, and induces symptoms including defoliation, fruit discoloration and fruit drop [2].…”
Section: Introductionmentioning
confidence: 99%
“…On citrus, P. citri damages plants by feeding on roots, bark, foliage and fruit [2]. During feeding P. citri injects toxic saliva into plants and extracts phloem sap, and induces symptoms including defoliation, fruit discoloration and fruit drop [2]. In addition, P. citri secretes copious amounts of honeydew leading to the development of sooty mold which also leads to reduced fruit quality and lowered plant vigor through the loss of photosynthetic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the WAO process catalyzed the high solubilization of the hemicellulose sugars from the solid fraction but was unable to result in cause a major hydrolysis of the solubilized hemicellulose molecules into monosaccharides [25]. The heavy metals were analyzed using ICP-OES indicated that Ag, Pb, Hg were not detected which could be inhibitory to the enzymes during enzymatic hydrolysis [26].…”
Section: -2 Liquid Fraction Post Wet Air Pretreatmentmentioning
confidence: 99%